Lifestyle habits among Najran University students, Najran, Saudi Arabia - Al-Qahtani, Awad Mohammed (Frontiers in Public Health, 2022)
Background: Unhealthy lifestyles have been linked to increased cardiovascular disease, diabetes, and other noncommunicable diseases. Objectives: The study aimed to estimate the prevalence of healthy eating habits; determine the prevalence of physical activity habits; to estimate the smoking habits among male students at Najran University, Saudi Arabia. Methods: In a cross-sectional study, a convenient sample of male university students from health sciences colleges were requested to answer a self-administered questionnaire about eating habits, physical activity, and tobacco smoking habits. Results: 454 male students from Najran university participated in this study. The majority (74%) were aged 21 years and above, unmarried (94.9%), had healthy BMI (47.4%), and suffered mild (41.4%) to moderate (32.4%) levels of stress during the previous month. The study findings showed a low daily frequency of consumption of vegetables and fruits. It varied from 16.07% of daily vegetable consumption to 11.23% daily fruit consumption. More than 10% of all students reported no consumption of fruits and vegetables. Students who felt severely stressed during the previous month were significantly not eating any vegetables and fruits. Furthermore, nearly half of students (47.5 %) were performing daily 30 minutes physical activity.. None of the participants' variables were significantly associated with routine physical activity. In addition, the study showed a relatively high prevalence of smoking (25.77%) among Najran university male students. The participants' age, overall health and level of stress experienced during the last month were significantly associated with the length of exposure to secondhand smoke. Whereas smoking any tobacco daily was significantly related to the age of participants. A high number of participants aged 21 years and above were significantly (P=0.019) exposed to secondhand smoke. Conclusion: To conclude, the study findings showed a low daily frequency of consumption of vegetables and fruits, a relatively high prevalence of smoking and a low level of awareness regarding the health risks of smoking; and a large number of participants were physically inactive among male university students. Intervention programs in university students should concentrate on improving nutrition attitudes and knowledge toward good diet, tobacco-smoking cessation strategies, and structured intervention programs to encourage physical activity.